The aestheticism of the rhyme in Duabul al Khuzaii's Taiyyah poem "Tajawabna bi al IrnaniwaZafrat" - nour, sakina; farez, fatima (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
علمية متكاملة، خصوصا من الجانب الصوتية This study reveals some semantics that differ with the phonetic system, as the transformations, shapes, and succession of the phonetic structures are among the important factors that shape the semanticity and direct the efficiency of the poetic discourse, where the sounds overlap within a special phonetic system to form terms related to their poetic context and express the experience of the poet, mainly that each experience has a special phonetic system that suits the poetic purpose. We chose the experience of Duabul al Khuzaii to be the subject and semantics of the phonetic research in this study because his poem shows a phonetic wealth. Besides, he: - Is one of the prominent poets of the 02nd and 03rd Hijri centuries. -Has a deep specificity and a different experience than of his contemporary poets thanks to his genesis and intellectual, political, and social trends that affected his experience and phonetic rhyme. - Has not been subject to a complementary scientific study, mainly regarding the phonetic aspect.